Elastoplastic Analysis for Circular Tunnel Based on Modified Lade Criterion considering Strain Softening and Dilatancy - Yansheng Deng; Jianxiu Wang; Baoping Zou (Advances in Civil Engineering)
Modified Lade criterion can not only describe the strength properties of many kinds of rocks well but also has simple and practical parameters. Although the elastoplastic solution of circular tunnel has been extensively investigated, the method based on modified Lade criterion considering the effect of the intermediate principal stress, strain-softening behavior, and dilatancy has not yet been studied. In this paper, a new numerical procedure based on modified Lade criterion is proposed to calculate the elastoplastic solutions for surrounding rock of the circular tunnel. The comparisons of stress, displacement, and plastic zone radius are carried out between the presented method and published literatures under axisymmetric and nonaxisymmetric original in situ stress field. Finally, a series of parametric analyses are executed and discussed. It can be concluded that the lateral pressure coefficient, λ, influences both the size of plastic zone and the development direction. The plastic zone radius shows a negative power function change with increasing critical deviatoric plastic strain and increases slightly with increasing dilation angle, ψ.